2017
DOI: 10.1103/physrevb.95.224428
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and direct observation of ferrimagnetism in multiferroic hexagonal YbFeO3

Abstract: The magnetic interaction between rare-earth and Fe ions in hexagonal rare-earth ferrites (h-REFeO3), may amplify the weak ferromagnetic moment on Fe, making these materials more appealing as multiferroics. To elucidate the interaction strength between the rare-earth and Fe ions as well as the magnetic moment of the rare-earth ions, element specific magnetic characterization is needed. Using X-ray magnetic circular dichroism, we have studied the ferrimagnetism in h-YbFeO3 by measuring the magnetization of Fe an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
(94 reference statements)
2
18
0
Order By: Relevance
“…While the size of Sc 3+ and Fe 3+ are close enough, there can be anti-site mixing where Fe 3+ goes to the R sites. If the moments of Fe 3+ on the R site tends to anti-align with those on the normal Fe sites as like in hexagonal YbFeO 3 , 48 the negative magnetization becomes possible. However, the negative magnetization is occurring only in the ZFC mode in LSFO.…”
Section: Resultsmentioning
confidence: 99%
“…While the size of Sc 3+ and Fe 3+ are close enough, there can be anti-site mixing where Fe 3+ goes to the R sites. If the moments of Fe 3+ on the R site tends to anti-align with those on the normal Fe sites as like in hexagonal YbFeO 3 , 48 the negative magnetization becomes possible. However, the negative magnetization is occurring only in the ZFC mode in LSFO.…”
Section: Resultsmentioning
confidence: 99%
“…Yb 3+ in YbFeO 3 ceramics has lone-pair electrons, the super-exchange interaction between Yb 3+ and Fe 3+ may introduce more complicated magnetic structures and physics. 11,25 Therefore, it should be an important issue to investigate Yb 1−x In x FeO 3 system in order to get a deeper and general physical understanding on h-RFeO 3 ceramics. Moreover, though the topological vortex domains in hexagonal RFeO 3 / RMnO 3 thin films and single crystals have been well investigated, [26][27][28] the domain structure in hexagonal ceramics has been rarely reported and there are several issues to be figured out.…”
Section: Methodsmentioning
confidence: 99%
“…No references were found on modeling of the PIP process for CMCs, though experimental studies on this manufacturing process have been reported. Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructured ferrites, in particular REE orthoferrites (RFeO3, where R = Sc, Y, Ln), can be used as the basis for such materials. These compounds have been actively studied due to their practically significant structural [4], magnetic [5][6][7][8], electrical [8][9][10], conducting [11] and photocatalytic properties [12][13][14]. In particular, ytterbium orthoferrite YbFeO3 has important for practical applications electrical and magnetic properties that change depending on its crystal structure [15].…”
Section: Introductionmentioning
confidence: 99%